Association of HIV status with infection by multiple HPV types (2018)
Objectives: To identify the clinical and demographic characteristics of HIV-positive and HIV-negative women infected by multiple HPV types. Methods: 1399 women participated in the study (240 HIV-positive and 1159 HIV-negative women). Samples were provided for Pap tests and for HPV detection and typing by PCR. Data were collected on HPV infection, frequency of multiple infection, and HPV type distribution. Odds ratios were reported from logistic regression models. Results: Compared with HIV-negative women, HIV-positive women had higher frequencies of cervical abnormality (30% vs. 20.8%), higher HPV prevalence (68.3% vs. 51.3%) and were more commonly infected with multiple HPV types (78.7% vs. 44.3%). HPV-16 was the most common type detected in the study population, with other types showing variable associations with HIV status. Positive associations were observed between infection by multiple HPV types and HIV status, cervical abnormality and having had more than three pregnancies. The odds of multiple infection by HPV types were higher in HIV-positive women who used an intrauterine device, who had a history of abortions and who had HIV viral loads and gt;100 000 copies/ml, whilst the odds were lower in women with and gt;500 CD4 cells/mm 3 . Conclusions: HIV immunosuppression favours infection by multiple high-risk HPV types, mainly in women affected by low-grade squamous intraepithelial lesions. Antiretroviral therapy had no effect on infection by multiple HPV types. Risk factors related to progressive damage to the cervix were positively associated with infection by multiple HPV types in women living with HIV. © 2018 John Wiley and Sons Ltd